Deterministic Inventory Routing Problem (DIRP): A Literature Review - Mohd Kamarul Irwan Abdul Rahim; Afif Zuhri Muhammad Khodri Harahap (International Journal of Supply Chain Management, 2017)
Vendor managed inventory (VMI) is a management policy in which the supplier implements the responsibility of maintaining the inventory at the retailers while confirming that they will not run out of stock. Under the VMI policy, the supplier will take a responsibility for managing the retailers. Moreover, the delivery times to the retailers are no longer agreed in response to retailers' orders; instead the supplier indicates when each delivery takes place. Therefore, this study reviews the main papers on the single item related to deterministic inventory routing problem (DIRP). Under this approach, the delivery of order emphases with deterministic demand rates. The objective of the DIRP is to resolve a flow strategy that can minimizes operational cost and inventory holding costs without having a stock-out according to a planning schedule. In this study, we have also focused on the single-warehouse, multiple-retailer vendor managed inventory (SWMR-VMI) where all retailers face a deterministic and constant demand rate.